Media and protection of human rights: Newspaper frames of Armed Forces human rights abuse of civilians in Nigeria - Ngozi Bibian Okeibunor et al. (Ianna Journal of Interdisciplinary Studies, 2021)
Background: Nigeria is one of the countries with the highest cases of human rights abuse. There are many instances of human rights abuse of innocent civilians by the Nigerian military.